Increasing Elementary School Students’ Science Learning Outcomes through the Inquiry Approach - Nadrah, Nadrah (Jurnal Basicedu, 2022)
This action research aims to determine how much increase in learning activities and learning outcomes of fifth grade students at SD Negeri Mangkura III Makassar. The inquiry approach in science learning is used in this study. The subjects of this study were fifth grade students of SD Negeri Mangkura III Makassar, with a population of 29 people consisting of 17 male students and 12 female students. This research was carried out in three cycles and each cycle consisted of four main components, namely: (1) action planning, (2) action implementation, (3) observation and evaluation, and (4) analysis and reflection. To collect data on learning outcomes used observation sheets. Furthermore, the data obtained were analyzed using qualitative and quantitative analysis. The results of the study revealed that learning activities and learning outcomes in science learning with an inquiry approach had increased. This is evidenced by the increase in the average score obtained and the high percentage of students who have very high learning outcomes, as well as the increasing percentage of student learning activities.